Specific mechanical properties of highly porous Ti-Zr-Mo-Sn shape memory alloy for biomedical applications. (1st July 2023) - Kim, Yeon-wook
Abstract: Porous Ti-5Zr-3Mo-6.5Sn (at.%) shape memory alloy scaffolds were fabricated by fiber-sintering. Microstructural morphology of the scaffolds showed high density of three dimensional and interconnected pores ranging from 100 to 500 μm in diameter. β →α " martensitic transformation, which is induced by the applied stress, occurs at human body temperature. The porous shape memory alloy scaffold has excellent superelasticity and then exhibited the strain recovery ratio of 90%. An elastic modulus of the Ni-free shape memory alloy scaffold, which was prepared by fiber-sintering, was as low as 19 GPa due to the high density of pores. These mechanical properties of low elastic modulus and superelasticity matched well with those of human bone. Considering the specific mechanical properties, structural morphology and biocompatibility, the fiber-sintered Ni-free shape memory alloy scaffolds satisfy the major requirements of bone substitutes for damaged or diseased bones. Graphical abstract: Image, graphical abstract